KAOMBO (Kearifan Lokal Buton tentang Hutan dan Lingkungan) - La Ode Muhammad Deden Marrah Adil (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2013)
Management of land, forest and environment by companies (corporations/investors) and State-Owned Enterprises (BUMN) under the guise of legislation such as Hak Guna Usaha (HGU) and Forest Management License (HPH) are operated at the expense of the local people. As a result, the local people are economically segregated since the land that they had cultivated for generations has been taken over by the owners with large capital who influenced the making of policy. Even worse, land annexation, logging, theft and inappropriate management of forest continue to occur as forms of public resistance. Illegal logging and hunting widespread on the basis of economic trouble along with difficulties in life that forces them to great lengths to exploit the available natural resources in the forest.Keywords: Kaombo, Forest,Butonese Local Wisdom